Literature Review of Renewable Energy Policies and Impacts (European Journal of Marketing and Economics, 2019)
By 2017, 128 countries have adopted renewable energy support policies, compared to just 48 countries in 2005. These policies played a crucial role in helping countries to shift from conventional energy to renewable energy by overcoming the barriers facing the development of renewable energy. This paper reviews the studies, which outlined the policies used by different governments to support the development of renewable energy, which includes: Tax incentives, Loans, Feed-in tariff, and Renewable portfolio standard. The literature review covers different studies that examined the impacts of renewable energy on economic growth, job creation, welfare, CO2 emissions, electricity prices, and fuel imports. Researches have used different methodological approaches, different periods, and different countries to examine the impacts of renewable energy. The studies found that the policies used were essential to shift to renewable energy substantially reduced carbon emission, and the majority concluded that renewable energy has a positive correlation with economic growth, job creation and welfare
Keywords: renewable policy, Feed-in Tariff (FiT), impacts, economic growth, CO2 emissions.